A new method for reconstructing the 3D shape of single cells in fruit. (December 2022) - Zhang, Meishuan; Yang, Jun; Wang, Yiheng; Li, Zhiguo; Tchuenbou-Magaia, Fideline
Graphical abstract: Highlights: A bio-microscope was developed to obtain three views of a single fruit cell. The CAD-based 3D geometric modeling method was proposed for reconstruction. The reconstruction method in the 3D single fruit cell shape was well validated. This method can find applications in other fields such as human and animal cells. Abstract: Fruit cells' shape generally reflects the physiological state and quality of the fruit, and indirectly dictates its economics. In this study, a new bio-microscope including three independent and orthogonal channels of opto-electromechanical microscopic observation systems was developed to obtain the three views (e.g., front view, top view, side view) of a single fruit cell using tomato and strawberry at two ripening stages as fruit samples. The obtained three-view images were used to reconstruct the 3D real shape of a single cell based on the 3D geometrical modelling method using Solidworks CAD design software and then compared with the actual geometric size. The average relative errors for the major diameter, minor diameter 1, minor diameter 2, projection perimeter and projection area were 4.04 %, 6.25 %, 5.71 %, 1.69 % and 3.79 %, respectively. This good accuracy makes the newly developed bio-microscope together with the proposed 3D geometrical modelling method a promising 3D shape reconstruction technology for a single fruit cell to extract real and detailed cell morphology information. Furthermore, this method can find applications in other fields such as human and animal cells where soft particles' 3D shape analysis is important.